-7+6p=-97

Simple and best practice solution for -7+6p=-97 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -7+6p=-97 equation:


Simplifying
-7 + 6p = -97

Solving
-7 + 6p = -97

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '7' to each side of the equation.
-7 + 7 + 6p = -97 + 7

Combine like terms: -7 + 7 = 0
0 + 6p = -97 + 7
6p = -97 + 7

Combine like terms: -97 + 7 = -90
6p = -90

Divide each side by '6'.
p = -15

Simplifying
p = -15

See similar equations:

| X+x+(x-4)+(x-4)=72 | | -(2r+7s)+2(r+s)= | | 12/6*5 | | x-1.6=-2.5 | | -6(a-3)-7(5-4a)= | | 1/42/7 | | -9x-11y-8x+12y= | | 14-m/2=10 | | -5x-10=2-[x+4] | | 4-5a=4(1+8a) | | 4x^2^4-16x^4/12ux^5 | | 45/17 | | 7r+5=11 | | V=3812 | | X-6-20=142 | | 6b+16=4 | | 25*w*1=0 | | 6[3a+1]-30=3[2a-4] | | 15+2x=2x | | 5x+2(5x-15)=-60 | | I2/3z=9 | | 11-(9x)+2x-(-9)= | | r=d/1-t | | (-t/2)=12 | | 7*z*0=0 | | -11=4a-3 | | -8(1-7n)+7(n+3)= | | 5n-3n+7+2n= | | 24a+72b-40c= | | 13*0*p=0 | | 6j-4j+12=6j-3j+30 | | 42-48v=-54 |

Equations solver categories